Good Practices in Addressing Gender Based Violence (GBV) in Zanzibar gender based violence committees at national and local level - Meena, Ruth; Ministry of Social Welfare, Youth, Women and Children Development (Zanzibar Ministry of Social Welfare, Youth, Women and Children Development, 2010)
This study intends to document good practices in addressing Gender Based Violence in Zanzibar. The thrust is to draw lessons from such practices as well as strengthen the various initiatives in combating GBV. In determing good pratices this study was guided by various international studies partucularly commissioned by UN agencies responsible for Human Rights, generally on Human's Rights and some especially on women and children's rights. The study considered the legal and policy enviroment that prohibits discriminatory practices on grounds of gender, criminalizes GBV, protects victims of GBV, and has Zero tolerance policies on GBV as necessary precondition for interventions which contain elements of good practices in GBV. While gender based violence affects men and women, girls and boys, women and children tend to be more vulnerable to GBV
Keywords: Gender based violence, Policy Frame Work Zanzibar